Representações sociais dos professores das creches das Universidades Federais paraibanas sobre arte na educação infantil - Lima, Norma Maria de (2015)
This thesis was carried out at the Pediatric Education at the Children Education Unit (UEI) of the Federal University of Campina Grande (UFCG) and School of Basic Education (EEbas) of the Federal University of Paraíba (UFPB), and had as target to know the social representations of teachers about the Art in Education for Children, identify practices and artistic skills developed in educational institutions investigated, and reflect on the art contributions to the integral development of the child. We defend the thesis in which the concept the teacher of early childhood education has of art and its implications for the overall development process of the child, are reflected in their pedagogical ways with the artistic languages. The theoretical foundations of this methodological investigative study were qualitative research which uses the theoretical and methodological framework of Social Representation Theory in the Moscovician perspective, which allowed us to approach the subjectivity of the participants and thus access to their representations. The survey data was constructed from the results collected from interviews with 11 teachers of schools / kindergartens. We chose to do a data merge with quantitative and qualitative resources used for triangulation that allowed a broader view of the phenomenon studied. Data was analyzed qualitatively, with the Bardin content analysis technique and showed that teachers shared the same representations of art, which can be explained by educational experiences and common experiences with art in action education with young children. We highlight some representations found: Art is an area composed of various knowledge specific languages; the art is human communication and expression; or that art is everything that is created by man; teaching art is an educational activity, mediation, facilitating tool in the teachers repertoire of pedagogical practice; Art interferes with the development process and formation of children through the development of creativity, autonomy, as well as its self value; freedom of expression, broadens their world view, among others. The present work does not exhaust the possibility of future studies on the subject. However, we hope that it will contribute to the discussions on working with art in children's education and their contributions to the integral formation of the human being.